Utilizing oil palm sterilization condensate as methylene blue adsorbent - Zaini, Ahmad Syahmi; Abdul Rahim, Nurul Aishah; Putra, Nicky Rahmana; Mohd Faizal, Azrul Nurfaiz; Zaini, Muhammad Abbas Ahmad (Taylor and Francis, 2026)
This study explores the transformation of oil condensate waste (OCW) into activated carbons (ACs) as an efficient solution for managing condensate waste within palm oil mill, while providing a sustainable alternative for dye removal from wastewater. OCW was chemically activated using sulfuric acid (CH samples) and zinc chloride (CZ samples), followed by comprehensive characterization of their elemental composition, surface chemistry, and textural properties. The resulting activated carbons exhibited specific surface areas ranging from 427.85 to 493.42 m2/g with the maximum adsorption capacities of 230.5 mg/g. Adsorption performance was evaluated using isotherm and kinetic models, with the pseudo-second-order model providing the best fit, indicative of a chemisorption mechanism. Thermodynamic parameters further revealed that the adsorption process was both endothermic and spontaneous in nature. The results demonstrate the potential of activated carbons derived from OCW as efficient and sustainable adsorbents for wastewater treatment applications.